Al ‘Alāqāt Ad Dalāliyyah Fī Al Lugah Al ‘Arabiyyah - Abdul Hafidz Zaid (Lisanudhad: Jurnal Bahasa, Pembelajaran dan Sastra Arab, 2018)
The transformational doctrine founded by Chomsky has given us the ability to form countless sentences, and thus the linguistic researcher’s mission is to subject all these sentences to those limited linguistic rules, and the completion of this work cannot be achieved only by converting the form of a formula or some sentences to another formula (from the passive to the active voice, for example), so that all those sentences are subject to certain rules. The relationship between words and their meanings contains four possibilities: either these words refer to meanings in themselves, God’s status to them, or to the placement of people, or to some by God and the rest by the status of men. Studies and research at the semantic level depend on the nature of the semantic relationships of words, and that the identification of the nature of the semantic relations of the words within the same language, as well as linguistic and non-linguistic means to determine the meaning, is one of the foundations of the study of semantic areas and identify the distinguishing features between the words contained in each of these areas. There are many types of semantic relations between the vocabulary, including: the relationship of tandem, the relationship of verbal participation, and the relationship of antagonism (or opposites in the language of the ancients).